2011
DOI: 10.1128/iai.05503-11
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Interactions between the Cholera Toxin A1 Subunit and ERdj3/HEDJ, a Chaperone of the Endoplasmic Reticulum

Abstract: Cholera toxin (CT) is endocytosed and transported by vesicle carriers to the endoplasmic reticulum (ER).The catalytic CTA1 subunit then crosses the ER membrane and enters the cytosol, where it interacts with its Gs␣ target. The CTA1 membrane transversal involves the ER chaperone BiP, but few other host proteins involved with CTA1 translocation are known. BiP function is regulated by ERdj3, an ER-localized Hsp40 chaperone also known as HEDJ. ERdj3 can also influence protein folding and translocation by direct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…From these results we concluded that CTA1 has partially disordered secondary structure and can be placed in the intrinsically disordered (ID) protein class. The behavior of cholera toxin A1 polypeptide of regular units of helices and β-sheets interrupted by coils were in close agreement to the work of Ampapathi et al [16] who observed the secondary structure through circular dichroism spectroscopy and 2D nuclear magnetic resonance spectroscopy and that of others [13][14][15][16].…”
Section: Secondary Structure Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…From these results we concluded that CTA1 has partially disordered secondary structure and can be placed in the intrinsically disordered (ID) protein class. The behavior of cholera toxin A1 polypeptide of regular units of helices and β-sheets interrupted by coils were in close agreement to the work of Ampapathi et al [16] who observed the secondary structure through circular dichroism spectroscopy and 2D nuclear magnetic resonance spectroscopy and that of others [13][14][15][16].…”
Section: Secondary Structure Analysissupporting
confidence: 76%
“…The A-subunit (CT-A, MW ~ 27,400) is the enzymatic domain [10,11], it contains 240 amino acid residues. The first 132 amino acids formed a compact globular unit composed of a mixture of α-helices and β-strands [10,12,13]. The catalysis is thought to occur in well define fissure on the free surface of A-subunit [10,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…52. After establishment of a baseline measurement (0 refractive index unit; RIU) corresponding to the mass of the sensor-bound CTA1, Hsp90, ARF6, or other ligands were perfused over the CTA1-coated sensor slide.…”
Section: Methodsmentioning
confidence: 99%
“…While a J-protein called ERdj3 has been implicated in SV40 infection (5), NEFs have yet to be demonstrated to be involved in this process. In fact, more generally, very little is known regarding NEF functions during ERAD (21), in contrast to J-protein functions (22)(23)(24)(25).…”
mentioning
confidence: 99%